2016
DOI: 10.1111/ele.12692
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐dependent selection for rare genotypes promotes genetic diversity of a tropical palm

Abstract: Negative frequency-dependent selection among species is a key driver of community diversity in natural systems, but the degree to which negative frequency-dependent selection shapes patterns of survival and genetic diversity within species is poorly understood. In a 5-year field experiment, we show that seedlings of a tropical palm with rare genotypes had a pronounced survival advantage over seedlings with common genotypes, with effect sizes comparable to that of light availability. This 'rare genotype advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 62 publications
0
36
1
Order By: Relevance
“…We were not able to obtain tissue containing both maternal and paternal genetic contributions without destructively sampling the seed to access the embryo, which would make it impossible to track survival across the seed‐to‐seedling transition. In light of this, we focus in this study on the maternal genotype of each seed, which has been shown to be a predictor of the genetic rarity of the diploid leaf seedling tissue (Browne & Karubian, ). Taking a genetic sample from the outer seed coat does not affect O. bataua germination rates (Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We were not able to obtain tissue containing both maternal and paternal genetic contributions without destructively sampling the seed to access the embryo, which would make it impossible to track survival across the seed‐to‐seedling transition. In light of this, we focus in this study on the maternal genotype of each seed, which has been shown to be a predictor of the genetic rarity of the diploid leaf seedling tissue (Browne & Karubian, ). Taking a genetic sample from the outer seed coat does not affect O. bataua germination rates (Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…(). In this study, our goal was to use an array of microsatellite loci that are assumed to be selectively neutral to sample the genome‐wide genetic rarity of individuals, rather than identify specific loci under selection as in Browne & Karubian (). However, we acknowledge that in some cases, microsatellite loci may be under selection because of linkage with other loci under selection or because they have a functional role in gene expression (Koshi & King, ; Selkoe & Toonen, ; Putman & Carbone, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations